CCL2/MCP-1 signaling drives extracellular matrix turnover by diverse macrophage subsets - Henrik J. Jürgensen; Lakmali M. Silva; Oliver Krigslund; Sander van Putten; Daniel H. Madsen; Niels Behrendt; Lars H. Engelholm; Thomas H. Bugge (Matrix Biology Plus, 2019)
Macrophage plasticity, cellular origin, and phenotypic heterogeneity are perpetual challenges for studies addressing the biology of this pivotal immune cell in development, homeostasis, and tissue remodeling/repair. Consequently, a myriad of macrophage subtypes has been described in these contexts. To facilitate the identification of functional macrophage subtypes in vivo, here we used a flow cytometry-based assay that allows for detailed phenotyping of macrophages engaged in extracellular matrix (ECM) degradation. Of the five macrophage subtypes identified in the remodeling dermis by using this assay, collagen degradation was primarily executed by Ly6C−CCR2+ and Ly6C−CCR2low macrophages via mannose receptor-dependent collagen endocytosis, while Ly6C+CCR2+ macrophages were the dominant fibrin-endocytosing cells. Unexpectedly, the CCL2/MCP1-CCR2 signaling axis was critical for both collagen and fibrin degradation, while collagen degradation was independent of IL-4Ra signaling. Furthermore, the cytokine GM-CSF selectively enhanced collagen degradation by Ly6C+CCR2+ macrophages. This study reveals distinct subsets of macrophages engaged in ECM turnover and identifies novel wound healing-associated functions for CCL2 and GM-CSF inflammatory cytokines. Keywords: Collagen degradation, Extracellular matrix endocytosis, Fibrin degradation, Interleukin-13, Mannose receptor/CD206, uPARAP/Endo180